Metabolic Profiling of Obesity With and Without the Metabolic Syndrome - A Multi-Sample Evaluation : Supplementary material - Lind, Lars; Salihovic, Samira; Sundström, Johan; Elmståhl, Sölve; Hammar, Ulf; Dekkers, Koen; Ärnlöv, Johan; Smith, J. Gustav; Engström, Gunnar; Fall, Tove (Uppsala University, 2021)
Pdf file with a total of 5 Supplementary Tables:

Supplementary Table 1. An overview of metabolite differences between certain groups.
Supplementary Table 2. Pathway enrichment and topographical analysis for the 427 validated metabolites that differed between obese subjects without MetS and normal-weight without MetS.
Supplementary Table 3. Pathway enrichment and topographical analysis for the 196 validated metabolites that differed between obese subjects with and without MetS.
Supplementary Table 4. Relationships between metabolites and BMI and number of MetS components in the continuous analysis.
Supplementary Table 5. Pathway enrichment and topographical analysis for the 371 validated metabolites that differed between overweight subjects without MetS and normal-weight without MetS.
Supplementary Table 6. Pathway enrichment and topographical analysis for the 417 metabolites being related to BMI in subjects with no MetS components.

Pdf file revised 211202. The old version is archived.

The dataset was originally published in DiVA and moved to SND in 2024.

Pdf file with a total of 5 Supplementary Tables:

Supplementary Table 1. An overview of metabolite differences between certain groups.
Supplementary Table 2. Pathway enrichment and topographical analysis for the 427 validated metabolites that differed between obese subjects without MetS and normal-weight without MetS.
Supplementary Table 3. Pathway enrichment and topographical analysis for the 196 validated metabolites that differed between obese subjects with and without MetS.
Supplementary Table 4. Relationships between metabolites and BMI and number of MetS components in the continuous analysis.
Supplementary Table 5. Pathway enrichment and topographical analysis for the 371 validated metabolites that differed between overweight subjects without MetS and normal-weight without MetS.
Supplementary Table 6. Pathway enrichment and topographical analysis for the 417 metabolites being related to BMI in subjects with no MetS components.

Pdf file revised 211202. The old version is archived.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Metabolic Profiling of Obesity With and Without the Metabolic Syndrome - A Multi-Sample Evaluation : Supplementary material
Keywords: metabolomics; metabolomics; obesity; obesity; Medical Science; Medical Science; Epidemiology; Epidemiology; epidemiology; epidemiology; metabolic syndrome; metabolic syndrome; insulin resistance; insulin resistance; Endocrinology and Diabetes; Endokrinologi och diabetes